Eternity revisited: in pursuit of a national documentation strategy and a national archival system - Adrian Cunningham (Archives & Manuscripts, 2014)
As I sit down to write this thought piece in January 2014, our Canadian colleagues are preparing for a Canadian Archives Summit with the enviable title ‘Towards a New Blueprint for Canada’s Recorded Memory’.1 To me the most interesting word in this title is the word ‘new’. While the Canadian summit has been organised in response to the crisis associated with the removal of federal funding for their National Archival Development Program, Australians can nevertheless only look with wonder at another Commonwealth country with a federal system of government that has the luxury of an existing national blueprint for recorded memory – for surely one cannot create a ‘new’ blueprint if an old one does not already exist.